The Potray of the Main Characters in the Complete Works of O. Henry - Muhammad Hasby Ash-shiddiqy; Muhammad Natsir; Anjar Dwi Astuti (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2020)
This study aims to determine the depiction of the main character and also how the author describes the main characters in O. Henry's short stories collection. The method in this study is qualitative by using library research, the data for the research is all sentences and dialogues among the characters in the short story which are related to the characters' characterization. The steps to collect the data are: a) Reading the five title short stories of The Complete Works of O. Henry, b) Taking notes, the required expressions or sentences from the short story that contain the information about main characters., c) Identifying all sentences and dialogues in the short story to get the data, d) Choosing the data dealing with the problems that will be investigated, the writer used a content analysis method as the data analysis. The findings of this study reveal that In the five short story titles in the collection of short stories "The Complete Works of O. Henry" there are two methods of characterization and they are the direct method and the indirect method, the characterization method used in each of the short story titles. different, there are those who only use one method and those who use two methods. and then In five selected short story titles in the "The Complete Works of O. Henry" short story collection there are several main characters in each of the short stories, some of which have two main characters, 3 main characters, and some even have only one main character. This can be seen that the main characters contribute or become the center of conflict or plot in each of the short stories